A generation presents itself - Kurdija, Slavko (Teorija in praksa, 2011)
The article examines selected results of quantitative surveys of 9th grade primary school students and their parents in Slovenia. On the basis of the theory and characteristics of contemporary youth and their processing of social reality, it seeks to provide an image of how this generation feels and presents itself as well as how it is coping with the complex modern demands of reflexive life-courses. The empirical analysis focuses on selected indicators which illustrate how students are satisfied with some essential parts of their lives and provides on overall index of the satisfaction of the whole sample of students. Based on the empirical findings it also attempts to define this generation's most common strategy of processing the social reality.
Keywords: Mladina; Youth; Zadovoljstvo; Satisfaction; Schooling; Šolanje; Privacy; Zasebnost; Slovenia; Slovenija; učenci